2019
DOI: 10.1111/gcb.14858
|View full text |Cite
|
Sign up to set email alerts
|

Trends in tuna carbon isotopes suggest global changes in pelagic phytoplankton communities

Abstract: Considerable uncertainty remains over how increasing atmospheric CO2 and anthropogenic climate changes are affecting open‐ocean marine ecosystems from phytoplankton to top predators. Biological time series data are thus urgently needed for the world's oceans. Here, we use the carbon stable isotope composition of tuna to provide a first insight into the existence of global trends in complex ecosystem dynamics and changes in the oceanic carbon cycle. From 2000 to 2015, considerable declines in δ13C values of 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 71 publications
8
45
1
Order By: Relevance
“…However, these studies have shown a small magnitude of change in δ 13 C (e.g. −1.4‰ from 2004 to 2017 for elephant seals in Mestre et al, 2020; and −1.8‰ for three tuna species from 2000 to 2015 in Lorrain et al, 2020) in the direction of the Suess effect, compared with the mean increase in δ 13 C we present for South African SRWs from −23.76 ‰ in the 1990s to −20.98 ‰ in the 2010 (i.e. +2.78 ‰).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, these studies have shown a small magnitude of change in δ 13 C (e.g. −1.4‰ from 2004 to 2017 for elephant seals in Mestre et al, 2020; and −1.8‰ for three tuna species from 2000 to 2015 in Lorrain et al, 2020) in the direction of the Suess effect, compared with the mean increase in δ 13 C we present for South African SRWs from −23.76 ‰ in the 1990s to −20.98 ‰ in the 2010 (i.e. +2.78 ‰).…”
Section: Discussionmentioning
confidence: 95%
“…Disentangling whether a change in a consumer's stable isotope values represents a shift in foraging behaviour or a shift in isotopic baseline is challenging (McMahon et al, 2013b). However, the increase in δ 13 C in South African SRWs is unlikely to be due to ecosystem baseline changes, as it is both substantial and in the opposite direction to the general trend of decreases in oceanic baseline 13 C values (de la Vega et al, 2019;Hanson et al, 2009;Lorrain et al, 2020;Mestre et al, 2020;Newsome, Etnier, et al, 2007).…”
Section: Caveatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in the regional isotopic composition of baseline producers, or isoscapes, occurs due to nutrient input, dominating phytoplanktonic composition, and oceanographic conditions (McMahon et al 2013, Magozzi et al 2017, Lorrain et al 2019), and precludes the direct comparison of raw δ 13 C and δ 15 N between skate assemblages (Manlick et al 2019). Therefore, we calculated region‐specific estimates of trophic position (TP) using the R package tRophicPosition (Quezada‐Romegialli et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Functional trait-based diversity of phytoplankton is mostly unexplored throughout the ocean, even though this approach (functional trait diversity) gives ecological information about species in changing environments (stratification, nutrient availability, cell size, and community structure) (Lorrain et al, 2019;Tuerena et al, 2019). Global climate change may favor opportunistic plankton species (e.g., Van de Waal and Litchman, 2020).…”
Section: Introductionmentioning
confidence: 99%